FROM DEPENDENCE TO AUTONOMY: EFL STUDENTS’ STRATEGIC ENGAGEMENT WITH GRAMMARLY - Aji, Kresna Rahma; Mubais, Ahmad (Acceleration: Multidisciplinary Research Journal, 2025)
This qualitative case study explores how EFL students perceive and utilize Grammarly as a tool to foster grammar correction autonomy. The study involved ten English Education students from UIN Walisongo Semarang and employed interviews, classroom observations, and document analysis to analyze how students edit their work, depend on tools, and think about their own learning. Findings reveal that students view Grammarly as a confidence-boosting aid that enhances grammatical accuracy and encourages independent revision. Many actively combined Grammarly with peer input, grammar resources, and self-review routines, demonstrating emerging learner autonomy. However, challenges such as excessive reliance, vague feedback, and emotional frustration hindered more profound engagement. The study concludes that Grammarly can support grammar autonomy when learners utilize it critically and educators provide reflective guidance, suggesting that students require pedagogy that balances digital support with self-regulated learning.